Development of clump-on sonar flow meter using symmetry channel model - Krivonogov Aleksei; Taranenko Pavel Alexandrovich; Khan Afrasyab (International Journal for Simulation and Multidisciplinary Design Optimization)
In connection to methods developed for determining of “liquid–gas” volume-mass parameters, research has been carried out by a group of scientists from South Ural State University and University of Dundee, where the current manuscript presents a new method for measuring a liquid and gas flow rate. Method able to measure a turbulent flow convective velocity through the pipeline wall and volumetric flow rate of a liquid and gas. A brief description of G. Taylor's “frozen turbulence” hypothesis is given on the basis of which the method works. Main scientific problems associated with its proof in relation to the problem of determining the convection velocity of turbulence are identified. Mathematical modeling was performed in the CFD computational fluid dynamics package using the hybrid eddy-resolving turbulence model SBES to determine an optimal configuration of the experimental setup. This model contains 2-D symmetry domain to decries simulation time. In this article describe correlation between 2-D symmetry model and full-scale tests. Result of experimental tests are presented. Therefore, novelty of this investigation is noninvasive method for flow measurement and experimental confirmation that it works.